The black cardiac patient of South Peru Andean regions - Reátegui López, Luis (2000)
OBJECTIVE: To determine black cardiac characteristics at high altitude. MATERIAL AND METHODS: Medical records review of 7 Cusco (3500 m.a.s.l.) patients with chronic mountain disease and unfavorable evolution to "black cardiac" disease. All had clinical and hematological tests, thorax X-ray and EKG; six had respiratory tests. RESULTS: Main symptoms were dyspnea and marked face, fingers and toes cyanosis, nail deformity. Terminal phase included right cardiac failure (RCF) in 2 cases. There were 2 deaths, one due to RCF and another due to pulmonary and mesenteric thromboembolism. We found extreme values of 9,2 x 106 red blood cells, 25 g/dL hemoglobin and 82% hematocrit. All had slight to moderate cadiomegaly with right ventricular cavities compromise. EKG showed ventilatory or hypoxic chronic heart-lung patron. In 3 patients we found moderate pulmonary hypertension (average pressure 31,3 mmHg) and increase in pulmonary vascular resistance (398 dynes/s/cm3). All suffered ventilatory hypoxic depression. Pathology studies showed anatomical substrate consistent with moderate pulmonary arterial hypertension. CONCLUSION: Patients with chronic mountain disease present more polycythemia and erythrocythemia than pulmonary hypertension.